(untitled) (Bangladesh Journal of Livestock Research, 2022)
To reduce the load of infectious diseases including avian influenza, a community involving poultry biosecurity model was piloted in Bogura, a northern district of Bangladesh from 2013 to 2017 for developing flock immunity in breeder farm and the community reached chicken like a win-win situation. The experiment started by selecting a commercial breeder farm where about 30,000 poultry were kept and had a record of being affected by avian influenza. The activities were the assessment of the poultry population within a kilometer radius of the breeder farm, providing health care services by a trained poultry health worker, vaccinating all village native chickens in the area above against Newcastle disease (ND), and Fowl pox, monitoring the level of antibody after vaccination against ND, and identifying the causes of sickness and mortality. When any bird died with clinical signs of AI, all surviving birds from that flock were purchased and culled off that household poultry immediately (spot culling), and proper disinfection was done by supervising the health worker. Affected farmers are provided compensation by the breeder farm. The results showed that the overall flack immunity against ND in the 3rd year was 90% at the community level, whereas on the breeder farm, it was 95% and 97% respectively against ND and AI in the selected area. However, the village chicken mortality due to infectious disease was significantly reduced, and no mortality was recorded due to ND or Fowl pox. The poultry population in that area increased twice at the end of the project. There were 13 cases of A/H5N1 confirmed by rRT-PCR from village chickens in those surveyed areas, and no positive case was perceived on that commercial breeder farm. From the study, it was concluded that community biosecurity has a positive role in reducing infectious diseases, including avian influenza, in commercial farming. Bang. J. Livs. Res. Vol. 29 (1&2), 2022: P. 62-66